Rubber Agro-Industry Green Logistic Conceptual Model - Dede Rukmayadi; Marimin Marimin; Uhendi Haris; Mohamad Yani (International Journal of Supply Chain Management, 2016)
ABSTRACTGreen Logistic is a form of logistics model which takes into account the social and environmental aspects, in addition to the functional and economical aspects. The objectives of this research were to design a structural model of rubber agro-industrial green logistic, SIR 20 (Standard Indonesian Rubber 20) process logistic and design of product packaging of SIR 20 produced by crumb rubber agroindustry. This research was using system approach which was supported by ISM (Interpretive Structural Modeling), Green VSM (Value Stream Mapping) and Fuzzy Green QFD (Quality Function Deployment) techniques. The results of ISM analysis showed that in the objectives elements of green logistic model was key elements, which were reduce the environmental impacts of rubber agro-industrial business process, improve the quality of packaging design appropriate to consumer expectations and environmentally friendly, as well as increase institutional performance in the implementation of objectives achievement of the green logistics system. The results of Green VSM analysis showed that by improving the quality of raw material for rubber slab (bokar) can improve the energy usage efficiency by 11%, water usage by 25% and processing time by 2%, therefore the productivity of raw material use increases from 54% to 67%. The analysis results of SIR 20 packaging those consumers want, and environmentally friendly were ease factors in packaging SIR products, green packaging materials, ease of assembly process and packaging quality. Metal packaging material was suggested due to the ease in packaging SIR products and recyclable, while the main weakness was less energy efficient. Based on this attribute a conseptual green logistic model was proposed.Keywords: green logistics, bokar (raw rubber materials), rubber, ISM, GVSM, GQFD